2015
DOI: 10.1371/journal.pone.0127629
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Recombinant Erythropoietin on Plasma Brain Derived Neurotrophic Factor Levels in Patients with Affective Disorders: A Randomised Controlled Study

Abstract: The study aims to investigate the effect of repeated infusions of recombinant erythropoietin (EPO) on plasma brain derived neurotrophic factor (BDNF) levels in patients with affective disorders. In total, 83 patients were recruited: 40 currently depressed patients with treatment-resistant depression (TRD) (Hamilton Depression Rating Scale-17 items (HDRS-17) score >17) (study 1) and 43 patients with bipolar disorder (BD) in partial remission (HDRS-17 and Young Mania Rating Scale (YMRS) ≤ 14) (study 2). In both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 63 publications
(83 reference statements)
0
10
0
Order By: Relevance
“…Recently, clinical evidence of the procognitive potential of EPO has been proved by a randomized controlled trial (RCT) involving moderately depressed patients with treatment-resistant depression ( N = 40) [ 168 ]. EPO also down-regulated plasma BDNF levels in patients with treatment-resistant depression (TRD; N = 40) [ 169 ]. Taken together, these seven clinical findings ( Table 1 ) suggested that EPO may provide a therapeutic option for patients with depression.…”
Section: Epo In the Treatment Of Depressionmentioning
confidence: 99%
“…Recently, clinical evidence of the procognitive potential of EPO has been proved by a randomized controlled trial (RCT) involving moderately depressed patients with treatment-resistant depression ( N = 40) [ 168 ]. EPO also down-regulated plasma BDNF levels in patients with treatment-resistant depression (TRD; N = 40) [ 169 ]. Taken together, these seven clinical findings ( Table 1 ) suggested that EPO may provide a therapeutic option for patients with depression.…”
Section: Epo In the Treatment Of Depressionmentioning
confidence: 99%
“…More and more experimental compounds are also being confirmed as capable of regulating depressive progresses via activating the BDNF signaling pathway ( Osborn et al, 2013 ; Yang et al, 2015 ). More importantly, the hippocampal BDNF and other neurotrophic factors have been shown to be reduced in patients with bipolar disorder and major depression ( Polyakova et al, 2015 ; Vinberg et al, 2015 ). Therefore, increasing BDNF protein expression might be a common pathway for antidepressants to exert their therapeutic actions, and searching agents that can increase BDNF protein expression is beneficial for the development of new antidepressants.…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant erythropoietin was characterized as a tissue protective factor (Elliot and Sinclair 2012, Rocha et al 2015, Vinberg et al 2015. Protective effect of erythropoietin is dose-dependent and receptor-dependent.…”
Section: Recombinant Erythropoietin (Epoetin)mentioning
confidence: 99%